Penerapan Kegiatan Market Day Dalam Membangun Karakter Percaya Diri Anak Di TK Insan Mulia Sungai Abu - Sari, Citra Purnama; Kusayang, Titin (UIN Sultan Maulana Hasanudin Banten, 2025)
This study aims to analyze the role of Market Day activities in building self-confidence in early childhood at TK IT Insan Mulia Sungai Abu. The approach used is qualitative descriptive with observation, interviews, and documentation methods. The results of the study show that Market Day provides a fun learning experience while fostering children's self-confidence. Through this activity, children learn to communicate, interact, and develop social skills and independence. Children who were initially shy became more confident in speaking and promoting their products. Thus, Market Day serves as an effective method to enhance children's self-confidence and social skills from an early age.